Spin-Glass Behavior, Magnetic, and IR Spectroscopy Analysis of Multimetallic Compound Ni0.25Mn1.25[Fe(CN)6]·6.1H2O - Qing Lin; Xiaofang Liu; Yun He; Haifu Huang; Xingcan Shen (Journal of Spectroscopy)
Multimetallic Prussian blue compound Ni0.25Mn1.25[Fe(CN)6]·6.1H2O has been prepared by coprecipitation. The temperature-dependent magnetic susceptibilities show the magnet transition for the compound at 8.5 K. According to DC variable-temperature magnetic susceptibility paramagnetic Curie temperature θ is −9.32 K. The observed value of coercive field (Hc) and the remanent magnetization (Mr) for the compound are 0.32 KOe and 0.36 μB. According to study of zero-field-cooled (ZFC) and field-cooled (FC) magnetization curves and AC magnetization curves, there exists a spin-glass behaviour in the compound, which exhibits freezing temperature Tg=7.76 K, below magnetic transition TC=8.5 K; that glass behavior is termed “reentrant” spin glass.